Testing NTRK testing: wet‐lab and in silico comparison of RNA‐based targeted sequencing assays - Pfarr, Nicole; Kirchner, Martina; Leichsenring, Jonas; Glade, Julia; Endris, Volker; Kazdal, Daniel; Schirmacher, Peter; Stenzinger, Albrecht (Genes, chromosomes & cancer, 2020)
NTRK fusions involving three neurotrophic tyrosine receptor kinase genes NTRK1, NTRK2, and NTRK3 and a variety of fusion partners were identified as oncogenic drivers across many cancer types.